Chilling temperatures and controlled atmospheres alter key volatile compounds implicated in basil aroma and flavor - Rodeo, Arlan James D.; Mitcham, Elizabeth J. (Frontiers in Plant Science, 2023)
Use of basil in its fresh form is increasingly popular due to its unique aromatic and sensory properties. However, fresh basil has a short shelf life and high chilling sensitivity resulting in leaf browning and loss of characteristic aroma. Moderate CO2 atmospheres have shown potential in alleviating symptoms of chilling injury in basil during short-term storage but its effect on the flavor volatiles is unclear. Moreover, studies on basil volatile profile as impacted by chilling temperatures are limited. We investigated the response of two basil genotypes to low temperatures and atmosphere modification, with emphasis on the volatile organic compounds responsible for basil aroma and flavor. Leaves were stored for 6 days at 5, 10, or 15°C combined with three different CO2 atmospheres (0.04%, 5% or 10%). Basil volatile profile was assessed using headspace solid phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS). Leaves suffered severe chilling injury and greater loss of aroma volatiles at 5°C compared to 10°C and 15°C. More than 70 volatiles were identified for each genotype, while supervised multivariate analysis revealed 26 and 10 differentially-accumulated volatiles for ‘Genovese’ and ‘Lemon’ basil, respectively, stored at different temperatures. Storage in 5% CO2 ameliorated the symptoms of chilling injury for up to 3 days in ‘Genovese’, but not in ‘Lemon’ basil. Both chilling temperatures and controlled atmospheres altered key volatile compounds implicated in basil aroma and flavor, but temperature had a bigger influence on the observed changes in volatile profile.